Deteksi Faktor Resiko Penyakit Tidak Menular dan Penerapan Perilaku Hidup Bersih dan Sehat di Kantor Camat Padang Utara - Sri Nani Jelmila; Yuliza Birman; Dita Hasni; Vina Tri Septiana; Reski Akbar; Niken Oktavia (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Corona Virus Disease (Covid-19) has resulted in around 5.4 million deaths worldwide. The virus that causes COVID-19 continues to mutate with the latest variant known as Omicron. Hypertension and diabetes are the most common comorbidities in Covid-19. Prevention of infection and complications of Covid-19 can be done by implementing clean and healthy living behaviors and early detection of comorbid diseases. This community service activity aims to early detection of non-communicable diseases and provide education about a clean and healthy lifestyle which is very much needed during a pandemic so that the immune system can increase and avoid transmission and complications of Covid-19. This activity held on January 8, 2022 for 2 hours. The participants of the activity are people in the working area of the Padang Utara sub-district office, Padang City. The results of this activity showed that the participants' average blood pressure was within normal limits and the average blood sugar was in the prediabetes category. This activity has the impact of increasing public knowledge about risk factors for non-communicable diseases and clean and healthy living behavior during a pandemic so it can prevent infectious disease infections and avoid non-communicable diseases and their complications.